Influence of germanium substitution on dielectric and ferroelectric properties of Ba(Fe0.5Nb0.5)O3 ceramics - Kantha,P. (2015)
In this work, the influence of Ge4+ substitution on dielectric and ferroelectric properties of high dielectric BaFe0.5Nb 0.5O3 ceramics was studied. The BGFN powders with a formula BaGex(Fe0.5Nb0.5)1-xO 3 where x = 0.01, 0.015, 0.02 and 0.025 were produced via mixed-oxide method and subsequently calcined at 1100-1200°C for 4 h. To form the BGFN ceramics, the resulting powders were pressed into pellets and sintered at various temperatures from 1200 to 1350°C for 4 h in order to obtain the ceramic with maximum density under each condition. The phase formation, microstructure and electrical properties of these ceramics were investigated. It was found that the Ge4+ substitution played an important role on the change of crystal structures and the phase formation of the BFN ceramics. The appearance of peak shift and peak split in XRD patterns confirmed the structural change from cubic to monoclinic in the ceramic samples at higher Ge 4+ content. The ceramics with x ≥ 0.015 contained three phases of BGFN, Ba3Fe2Ge4O14 and BaGeO 3. The amount of each phase was depended on the concentration of Ge4+ where the Ba3Fe2Ge4O14 and BaGeO3 phases were found to increase with increasing x content. It was also found that the higher porosity and smaller grain sizes were found in the BGFN ceramics with higher level of Ge4+ addition. This in turn affected their dielectric properties where dielectric constant was substantially decreased while the dielectric loss was greatly improved. The optimum composition for this system was found to be x = 0.015, where the maximum dielectric constant (∼12282) with lower dielectric loss at room temperature were obtained. © 2013 IEEE.